A novel wide-bandgap small molecule donor for high efficiency all-small-molecule organic solar cells with small non-radiative energy losses. Issue 5 (8th April 2020) - Wang, Yulong; Wang, Yang; Zhu, Lei; Liu, Haiqin; Fang, Jin; Guo, Xia; Liu, Feng; Tang, Zheng; Zhang, Maojie; Li, Yongfang
Abstract : A novel small molecule donor based on thiazolo[5, 4- d ]thiazole (TTz) unit is developed for OSCs application with 13.9% power conversion efficiency and a small non-radiative energy loss of 0.18 eV. Abstract : In this work, a wide-bandgap small molecule donor, BTTzR, that incorporates the electron-donating alkylthienyl-substituted benzo[1, 2-b:4, 5-b']dithiophene (BDT-T) unit and the electron-deficient thiazolo[5, 4-d]thiazole (TTz) unit as the building block units is designed and synthesized. BTTzR exhibits strong absorption in the wavelength range of 400–650 nm with a wide optical bandgap of 1.88 eV, a low-lying highest occupied molecular orbital (HOMO) energy level of –5.58 eV, and an ordered molecular orientation and packing. Hence, optimized all-small-molecule organic solar cells (SM-OSCs) based on BTTzR as a donor and Y6 as an acceptor achieve an outstanding power conversion efficiency (PCE) of 13.9%, which is among the highest values reported in the literature to date. More importantly, the devices exhibit a very small non-radiative energy loss of 0.18 eV, which is similar to those of inorganic solar cells. These results indicate that BTTzR is a promising small molecule donor material for SM-OSC application and provide new insight into the design of photovoltaic materials to reduce the non-radiative energy loss in the OSCs.